Atypical fibroxanthoma arising in a young patient with Li‐Fraumeni syndrome. (24th December 2013) - Lee, Sun Mi; Zhang, Wei; Fernandez, Martin P.
<x xml:space="preserve">Abstract</x> Patients with Li‐Fraumeni syndrome (LFS) have a germ‐line mutation of p53 (TP53) and are predisposed to develop a variety of malignancies at an early age. In this report, we describe an 18‐year‐old woman with LFS who developed an atypical fibroxanthoma (AFX) on her left arm. This tumor was based in the dermis, sparsely cellular and had ill‐defined borders. It was composed predominantly of medium‐sized spindled‐shaped cells, but many large cells with pleomorphic nuclei were also present. Immunohistochemical stains showed that the tumor cells lacked expression of keratin, S‐100 protein, desmin and CD34. Array‐based comparative genomic hybridization (aCGH) revealed marked genomic instability with multiple whole chromosome losses, including chromosomes 8, 10, 13 and 22, as well as a partial loss of 17p. This represents one of a few reports of a cutaneous tumor in a patient with LFS and a rare example of an AFX occurring at a young age.